Psychological Capital as a Predictor of Organizational Commitment of Executive Board Administrators of Faculty at State University of Malang - Puspa Adelina, Rafika; Andrini Faridav, Ika (KnE Social Sciences, 2022)
Previous research on psychological capital and organizational commitment in education or student organizations is still very limited, and no research has been conducted during the transition period from pandemic to endemic. This study aims to determine the contribution of psychological capital to organizational commitment simultaneously and partially. The subject of this study is the management of the Faculty Student Executive Board at UM for the period of 2022. The instruments used are Meyer and Allen’s scale of organizational commitment and Luthans’ scale of psychological capital. The analysis of the research data used is multiple linear regression analysis. The results showed that the F-test = 12.873 (p < .05), which means that psychological capital (self-efficacy, resilience, optimism, and hope) had a concurrent effect on organizational commitment and the results of the coefficient of determination (R-squared) showed a contribution of psychological capital (self-efficacy, resilience, optimism, and hope) of 29.9%. The results of t-test showed that self-efficacy dimension t=3.190 (p < .05) and hope dimension t=2.583 (p < .05), which means that self-efficacy and hope have partially significant influence on organizational commitment. The results of the t-optimistic test are t=.660 (p > .05) and the resilience dimension t=.161 (p > .05), which means that it has no significant influence on organizational commitment. The contribution of effective self-efficacy donations was 16.20% and the effective contribution of hope was 10.10%. Suggestions for organizations or administrators to improve self-efficacy are to provide positive feedback, social recognition, to give management experience of mastery. Keywords: psychological capital, organizational commitment, management